PENGEMBANGAN PAKET WISATA KEBUGARAN DI DESA MAS, UBUD, GIANYAR - Valentia Anjeli; I Nyoman Sudiarta; I Ketut Suwena (Jurnal IPTA)
Wellness tourism was a type of tourism that was in great demand by local and international tourists. To increase tourist interest, one way was by choosing wellness tourism, and the activities were packaged in a varied and interesting way. This research referred to the development of thematic wellness tourism packages. The research aimed to determine the potential for wellness tourism in Mas Village and then package it thematically into a Mas Village wellness tourism package. This research used data collection techniques, including interviews, observation, documentation, and literature study. The data analysis technique used in this research was qualitative descriptive analysis. The results obtained from this research were that there were various wellness tourism potentials in Mas Village, which were then packaged thematically into a Mas Village wellness tourism package, including the Emotional Dimension package, Mas Cultural Tour (full-day tour); Spiritual Dimension, Mas Spiritual Tour (Half-day Tour); Mental Dimension, Mas Relax Tour (Half-day Tour); Environmental Dimensions, Rice Field Tracking (Half-day tour).